Analysis of the Role of the Indonesian Christian Student Movement (GMKI) Medan Branch in Improving Cadre Information Literacy through the Literacy Movement - Dwi Novia Sirait; Suwardi Lubis; Robert Sibarani (East Asian Journal of Multidisciplinary Research, 2022)
This study aims to analyze the role of the Medan branch of the Indonesian Christian Student Movement in increasing the information literacy of cadres through the literacy movement. Analyzing what factors are the drivers and barriers to the role of GMKI in increasing the information literacy of GMKI cadres through the literacy movement. The method of this research is descriptive research with a qualitative approach. Data collection techniques used interviews, observations and document studies. Based on the research, it was found that GMKI Medan Branch performs its role as a forum for learning, developing creativity to the application of knowledge through the provision of training programs through book review programs, book reviews, journalistic training, discussing topics that are developing in the community, and leadership training and others. The driving factor for GMKI's role in increasing cadre information literacy is the lack of literacy and communication culture that produces commitment. Meanwhile, the inhibiting factor for GMKI's role in increasing information literacy is the absence of a special program on the literacy movement. The conclusion shows that GMKI performs its role in increasing the information literacy of cadres even though it is in the basic stages. But this has answered one of the tasks of youth as agents of change.